URGENSI NEGARA INDONESIA MERATIFIKASI ICRW (THE INTERNATIONAL CONVENTION FOR THE REGULATION OF WHALING) UNTUK MELEGALKAN PERBURUAN PAUS SECARA ADAT (ABORIGINAL SUBSISTENCE HUNTING) DI INDONESIA (STUDI TENTANG PERBURUAN PAUS YANG DILINDUNGI DI DESA LAMALERA) - Socha Salsabila Riyadi; Maria Maya Lestari; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Indonesia has a well-known tradition of hunting whales in Lamalera Village, LembataIsland, East Nusa Tenggara, which has been carried out for hundreds of years for food needs.However, unlike countries where people also hunt lagoons, Indonesia does not have regulationsgoverning traditional hunting. In fact, Indonesia does not yet have regulations that provide adefinition of what traditional hunting is, either legally or customary law, and whether traditionalhunters may catch protected species.The type of research conducted can be classified as normative-juridical research wherethis research is more specific on the importance of the Indonesian state to ratify the InternationalWhaling Commission and the legal systematics of regional conventions and rules. The authoralso uses the principle of Free Prior and Informed Consent to ensure that the law and the rightsof indigenous and tribal peoples are guaranteed and respected.From the results of the research it was found that, first, there is no regulation regardingcustomary hunting in Indonesia so that the status of whaling carried out by the Lamalera peopleis still illegal. According to state law, Indonesia has not ratified the International WhalingConvention, which makes customary hunting status not recognized in international law.Keywords: Whaling, Aboriginal Subsistence Hunting, Indigenous People, EnvironmentalLaw, Urgency